2021
DOI: 10.3389/fonc.2021.638099
|View full text |Cite
|
Sign up to set email alerts
|

A Prognosis Marker SLC2A3 Correlates With EMT and Immune Signature in Colorectal Cancer

Abstract: SLC2A3 is a membrane transporter that belongs to the solute carrier family, whose function includes transmembrane transport and glucose transmembrane transport activity. To clarify the expression and role of SLC2A3 in colorectal cancer (CRC), we analyzed the TCGA and GEO databases and found that SLC2A3 mRNA levels were significantly higher in CRC tissues than that in adjacent non-tumor tissues. Furthermore, high expression of SLC2A3 predicted poor overall survival and disease free survival for CRC patients. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 49 publications
3
37
0
Order By: Relevance
“…A previous study in colorectal cancer showed that SLC2A3 could regulate the epithelial-mesenchymal transition (EMT) classical pathway and PD-L1-mediated immune responses (Gao et al, 2021), which was consistent with our research results. Unlike the findings of this study, the results of our functional enrichment analysis showed that SLC2A3 might be related to cytokine-cytokine receptor interaction, EMT, T cell receptor signaling pathway, B cell receptor signaling pathway, and immune checkpoints.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study in colorectal cancer showed that SLC2A3 could regulate the epithelial-mesenchymal transition (EMT) classical pathway and PD-L1-mediated immune responses (Gao et al, 2021), which was consistent with our research results. Unlike the findings of this study, the results of our functional enrichment analysis showed that SLC2A3 might be related to cytokine-cytokine receptor interaction, EMT, T cell receptor signaling pathway, B cell receptor signaling pathway, and immune checkpoints.…”
Section: Discussionsupporting
confidence: 93%
“…Gao et al revealed that SLC2A3 plays a significant role in the progression of colorectal cancer by affecting EMT and immune response. Furthermore, SLC2A3 may regulate the expression of PD-L1 [ 15 ]. An EMT signature performs well in predicting the overall survival, and the model is associated with immune infiltration, proving its potential role in regulating immune status [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“… Dai et al (2013) found that highly expressed miR-106a can hinder the effect of SLC2A3 and further inhibit cell proliferation and glycolysis in gliomas. In addition, the up-regulation of the SLC2A3 gene has also been observed to reduce the OS and Disease Free Survival of patients with colorectal cancer ( Gao et al, 2021 ). As a transcription factor that induces DNA damage, recombinant DNA damage inducible transcript 3 (DDIT3) can develop diseases through apoptosis and autophagy ( Liu H. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%